THE CONCEPT AND MEANING OF MATERIAL AND FINANCIAL SECURITY OF THE ACTIVITIES OF THE TERRITORIAL OFFICES OF THE STATE BUREAU OF INVESTIGATIONS (Bulletin of criminological association of Ukraine, 2023)
It is argued that material and financial support can be considered in two aspects - as a process and as a set of forms, methods and means. It is noted that, in general, both approaches do not contradict or exclude each other, but only reflect different sides of the researched provision. It is substantiated that the material and financial support of the activities of the territorial administrations of the DBR should be considered as the activity of competent subjects regulated by legal norms regarding the implementation of a complex of decisions and measures to search for sources, the formation of funds, the rational distribution and use of material (i.e. material) means and money for the purpose creation of favorable conditions for efficient, high-quality and impartial performance by the territorial administrations of the SBI of tasks, functions and powers assigned to them. It has been proven that the material and financial support of the territorial administrations of the DBR should include: 1) material and technical resources, which include: a) buildings and premises (office, residential, educational, health care, technical, etc.); b) transport and means necessary for its normal operation; c) furniture and stationery; d) computer equipment and office equipment; e) special equipment and facilities; e) weapons; f) means of encouraging and motivating personnel; 2) financial resources: a) funds for purchasing and paying for maintenance of material means; b) funds for payment and labor incentives of the staff of the territorial offices of the SBI; c) funds for the purchase of information, computer and other technologies; d) funds for training and
Keywords: material and financial support; territorial administration; State Bureau of Investigation